DETERMINAN PERMINTAAN KPR FLPP PADA PT. BANK BTN KANTOR CABANG SYARIAH - Stiorini, Lilis; Vietha Devia SS (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research aims to determine the effect of income, population, murabahah margin, mortgage interest rates at competing banks, and age on the demand for FLPP (Housing Finance Liquidity Facility) mortgages at PT. Bank BTN Syariah Malang for the 2020-2022 period using secondary data. The reason for choosing Bank BTN Syariah Malang is because Bank BTN Syariah occupies the second position in the category of the best KPR Subsidy distribution in Indonesia, which is 14,052 units. This research uses quantitative methods with multiple linear regression analysis. The results of the study prove that income variables have a positive and significant effect on the demand for FLPP home ownership loans. The variability in the number of married people and mortgage interest rates at competing banks has a negative and significant effect on the demand for FLPP home ownership loans. Meanwhile, murabahah margin and age variables do not significantly affect the demand for FLPP home ownership loans. The variables of income, population, murabahah margin, mortgage interest rates at competing banks, and age simultaneously affect the demand for home ownership loans, housing finance liquidity facilities.